Proceedings of the Workshop on Human-in-the-Loop Data Analytics 2016
DOI: 10.1145/2939502.2939505
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between user intention and model parameters for human-in-the-loop data analytics

Abstract: Exploratory data analysis is challenging given the complexity of data. Models find structure in the data lessening the complexity for users. These models have parameters that can be adjusted to explore the data from many different angles providing more ways to learn about the data. "Human in the loop" means users can interact with the parameters to explore alternative structures. This exploration allows for discovery. This paper examines usability issues of Human-Model Interaction (HMI) for data analytics. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…In contrast to explicit clustering systems, Andromeda [21] projects high-dimensional data into two dimensions using a method combining OLI with parametric interaction. Though similar data points implicitly cluster into groups, explicit clusters are not defined.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast to explicit clustering systems, Andromeda [21] projects high-dimensional data into two dimensions using a method combining OLI with parametric interaction. Though similar data points implicitly cluster into groups, explicit clusters are not defined.…”
Section: Related Workmentioning
confidence: 99%
“…Indications and feedback from previous studies [1,9] have shown that users favor clusters in the sensemaking process. These include systems with explicit clusters that are created to spatially organize information on the display (for example, iVisClustering [17]) and those that naturally develop due to the underlying layout updating through expressive interactions (for example, Andromeda [21]). It is therefore surprising that clusters are not explicitly defined in many OLI systems; rather, they implicitly exist in the layout structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…"What respect to what" was described as a usability issue with direct manipulations in interactive projections by Self et al [9]. This usability issue revolves around interpreting the analyst's intent accurately.…”
Section: Introductionmentioning
confidence: 99%